ナンキョク ニ オケル フユウ リュウシジョウ ブッシツ ノ ソクテイ - 唐沢, 栄; カラサワ, サカエ; 遠藤, 陽子; エンドウ, ヨウコ; 平野, 耕一郎; ヒラノ, コウイチロウ; KARASAWA, Sakae; ENDO, Yoko; HIRANO, Koichiro (国立極地研究所, 1976)
P(論文) The particulate matters suspended in the air were collected on a glass fiber filter by a slightly modified Hi-volume air sampler at Syowa Station, Antarctica from January 8 to February 4 in 1974. The sampling was also carried out at Yokohama City. Analysis were made at Yokohama City Institute of Health by using a gravimetric method, a scanning electron microscope and a X-ray micro analyser. The observations made by the scanning electron microscope and the X-ray micro analyser revealed the differences in form and component between the particulate matters collected at Syowa Station and at Yokohama City. From the results of the electron micrograph of the particulate matters suspended in the air at Syowa Station, the initial symptoms of air pollution around the station seemed to occur on the days when the work was done actively. departmental bulletin paper